Assistance in the Preparation of Research Grant Proposals for STAI Ihyaul Ulum Gresik Lecturers - Inayatur Rosyidah; Zeid B. Smeer; Taa'ib Maghfur; Sayyidaturrohimah (Jurnal Indonesia Sosial Teknologi, 2024)
Lecturers have the main task in carrying out the Tri Dharma of Higher Education, namely Education, Research, and Community Service. Through research, they contribute to the development of useful new theories and discoveries in various fields. However, until 2023, only 10.6% of STAI Ihyaul Ulum lecturers are actively involved in research and community service programs. The main obstacle faced is the limitations in formulating problems and preparing proposals in accordance with standards. To overcome this, an intensive training and mentoring program was held using the Participatory Research Action (PAR) method for 10 permanent lecturers. This program has succeeded in increasing participants' knowledge and understanding, but further assistance is needed so that participants are more proficient in compiling credible research and critical literature review.